Working in style : architecture + interiors - Uffelen, Chris van ([Salenstein] : Braun, 2016)
Gone are the times when offices were either huge factory-like spaces or tiny cell structures that were unimaginatively designed. Nowadays, they represent the identity of a corporation while also offering an inspiring workplace at the same time. Office design has developed into a complex discipline, which always tries to find new solutions to meet the needs of employees working in a diverse environment while supporting their motivation and productivity. This volume shows examples from around the world that not only incorporate the defining characteristics of an employer but also apply the latest findings of workplace research. The results are veritable office landscapes, ranging from the creatively designed work space of a start-up via a multi-functional subdivided office without fixed work stations, to elaborately equipped and prestigious office spaces. All projects contribute to understanding the future of office life.
Keywords: Office decoration -- Pictorial works; Interior decoration -- Pictorial works; Offices -- Designs and plans; Interior architecture -- Pictorial works; Office buildings -- Design and construction -- Catalogs